"Integración europea y cooperativismo: una reflexión sobre la sociedad cooperativa europea con motivo del año internacional del cooperativismo" (European integration and cooperativism: a reflection on European cooperative societies to mark the international year of cooperativism) - Santiago Larrazabal Basañez (Boletín de la Asociación Internacional de Derecho Cooperativo, 2012)
This study aims to make us aware of the importance that the spread of cooperatives has had on European integration, also approached from educational institutions and how their inspiring principles should penetrate more deeply into the «acquis communautaire» in the framework of this process. It offers an in-depth study of the endeavours made to this effect in the legal scope through Commission Regulation EC no. 1435/2003 of 22 July 2003, on the bylaws of European Cooperative Society (SCE) and Commission Directive 2003/72/EC of the same date, which completes the bylaws on European cooperatives concerning implications for workers. The study analyses the positive and negative points of this regulation and the implementation of the SCE from the time it started in 2003 to the present. It also proposes some measures to revitalise it, with the purpose of «socialising» the cooperative model in the process of European social integration, which is currently undergoing a severe crisis.